Global development - Hammett, Daniel, author.
1 online resource
Keywords: "How do we try to make the world a better place, when the challenges of poverty, disease, war, conflict, and climate change continue to impact millions of lives? Global Development: The Basics is a lively and engaging introduction to the shifting landscape of global development, right from its origins, to present-day problems, and on to what the future for global development might look like. Recognising global development as an economic, political and social project, this book tackles a series of critical questions: asking 'what' development is and how it is measured, where and to whom it is assumed to happen, how these approaches are developed, and whose benefit do they serve? The book invites readers to consider the complexities and challenges of the concept of development, including its historical roots in colonialism, and the geopolitical power relations which continue to set much of the agenda. It investigates whose voices are included or silenced in dominant approaches to development, and the growing importance of 'non-traditional' development funding and approaches. Covering key topics in the field, from economics and politics, through to gender and climate change, Global Development: The Basics is perfect for readers starting out in their understanding of global development"--